Regulation 805/2004 creating a European enforcement order twenty years after its approval: a reading from the jurisprudence of the Court of Justice of European Union - Rodríguez Vázquez, María Ángeles (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
This work analyzes the jurisprudence of the CJUE interpreting the problems posed by the practical application of Regulation 805/2004 creating a european enforcement order. The abolition of exequatur has not been carried out at the cost of the rights of the defence. However, it is an instrument little used and unknown by many legal operators.